2019
DOI: 10.1097/inf.0000000000002319
|View full text |Cite
|
Sign up to set email alerts
|

Viral Bacterial Interactions in Children: Impact on Clinical Outcomes

Abstract: Respiratory viral infections are associated with significant morbidity and mortality in children < 5 years of age worldwide. Among all respiratory viruses, respiratory syncytial virus (RSV) is the world's leading cause of bronchiolitis and pneumonia in young children. There are known populations at risk for severe disease but the majority of children who require hospitalization for RSV infection are previously healthy. Viral and host factors have been associated with the pathogenesis of RSV disease, however, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 48 publications
(51 reference statements)
1
16
0
Order By: Relevance
“…Another vaccine preventable illness which disproportionately affects infants with DS is respiratory syncytial virus (RSV) bronchiolitis. This pathogen is the primary cause of this illness, which accounts for significant number of hospital admissions and deaths throughout the world each year (104). Infants with DS are at increased risk for more severe disease independent of congenital heart disease status; one systematic review and meta-analysis reported a 9-fold increased mortality and 8.7-fold increase in risk of hospitalization (105) for infants with DS, and another recently backed this up reporting significantly increased admissions, length of stay and ventilatory requirement, again independent of CHD (106).…”
Section: Future Directionsmentioning
confidence: 99%
“…Another vaccine preventable illness which disproportionately affects infants with DS is respiratory syncytial virus (RSV) bronchiolitis. This pathogen is the primary cause of this illness, which accounts for significant number of hospital admissions and deaths throughout the world each year (104). Infants with DS are at increased risk for more severe disease independent of congenital heart disease status; one systematic review and meta-analysis reported a 9-fold increased mortality and 8.7-fold increase in risk of hospitalization (105) for infants with DS, and another recently backed this up reporting significantly increased admissions, length of stay and ventilatory requirement, again independent of CHD (106).…”
Section: Future Directionsmentioning
confidence: 99%
“…In a study undertaken amongst preschool children attending a day-care center the severity of the official SNOT score, denoting the degree of nasal discharge, during an apparent viral infection was not influenced by the type of virus but rather the presence and density of H Inf and Strep Pneumoniae cultured from the nose (78). Subsequent studies including studies of the resident microbiome have provided supporting evidence for the importance of both these organisms and others such as Moraxella in the generation of symptoms during an acute "viral" respiratory illness (79)(80)(81)(82)(83)(84). As we learn more about the interactions of bacteria, viruses, and other organisms as they seek to obtain an advantage in a given niche the more the discrete distinction between viral and bacterial infections break down.…”
Section: D) Viral-bacterial Interactionsmentioning
confidence: 97%
“…The traditional view that respiratory viruses are primary triggers of wheezing while bacteria are mostly linked to pneumonia is increasingly being re-evaluated. Several studies have shown the coexistence of virus and bacteria in the airways with important clinical and pathobiological implications [ 39 ]. A study including asthmatic children ( n = 361, 984 samples) identified that wheezing episodes were associated with both bacterial infection (odds ratio 2.9, p < 0.001) and virus infection (odds ratio 2.8, p < 0.001) [ 40 ].…”
Section: The Symbiosis Of Bacterial Microbiota and Respiratory Viruses In Early-lifementioning
confidence: 99%